SISTEM PENUNJANG KEPUTUSAN UNTUK MENENTUKAN GURU MADRASAH IBTIDAIYAH TERBAIK MENGGUNAKAN METODE SIMPLE MULTI ATTRIBUTE RATING TECHNIQUE (SMART) (STUDI KASUS : YAYASAN DARUL HIKMAH AL-AZHARIYAH) - Ivan Syah Putra; Anis Mirza (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Performance appraisal is the process of evaluating and assessing work performance. This activity can improve decisions on the performance of teachers and provide feedback to teachers to spur morale in improving their operations, dedication and performance so that they become better. Reward or award is a form of gratitude from the company for the dedication and performance of employees who have good quality work. The assessment process for selecting the best teacher currently given is still subjective in nature, only calculating the number of attendance in 1 month, even though in other aspects it has not been included in the assessment, this is because at this time there is no longer available media that processes teacher assessments in detail. The Simple Multi-Attribute Rating Technique (SMART) method is a multi-attribute decision-making method that can be used to support decision-makers in choosing several alternatives. In the process, the SMART method uses an adaptive linear model to predict the value of each alternative. The criteria used in the research are 3 aspects, namely discipline and professionalism. Disciplinary criteria include absenteeism, illness, permission, absence, lateness, and percentage of attendance, and professionalism criteria include teaching days and less working hours. This decision support system is expected to assist decision makers in providing incentives to the best teachers.